If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x(x-1)=2x-3+3x
We move all terms to the left:
3x(x-1)-(2x-3+3x)=0
We add all the numbers together, and all the variables
3x(x-1)-(5x-3)=0
We multiply parentheses
3x^2-3x-(5x-3)=0
We get rid of parentheses
3x^2-3x-5x+3=0
We add all the numbers together, and all the variables
3x^2-8x+3=0
a = 3; b = -8; c = +3;
Δ = b2-4ac
Δ = -82-4·3·3
Δ = 28
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{28}=\sqrt{4*7}=\sqrt{4}*\sqrt{7}=2\sqrt{7}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-8)-2\sqrt{7}}{2*3}=\frac{8-2\sqrt{7}}{6} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-8)+2\sqrt{7}}{2*3}=\frac{8+2\sqrt{7}}{6} $
| 8+45=a-53 | | 3x^2-7x+16=0 | | 7-2c=-3c | | -x+10=4x-15 | | 3a+10=65 | | x2+9x=0 | | 20n+6=n-374 | | .9=x/36 | | -10g=9-7g | | 1/8-8/9w=1/9w+9/8 | | -4(2x-3)+3x-5=-18 | | (2x-9)=15 | | 9w-6=3w+7 | | .90=x/36 | | -5(x+1)-11=13+6 | | -8+2r-6r=-8r-4r | | a-344=-9a-4 | | 5(2x-1)-4x-1=-12 | | -17x=-208 | | 200m-100m+57,300=60,900-200m | | -5=2x-13 | | .75=x/36 | | 3/5y+11=-1/3y+8 | | -9(10k+1)=-10(9k-1) | | 6z=4(1/2z-8 | | q+239=-5q-7 | | 9c-4c=4 | | 75=x/36 | | -20y/20=-20 | | 7x+9-6x=12 | | Y=10x+23/11 | | 6s+11s=4 |